Studien alpiner und montaner Oxypoda-Arten (Coleoptera: Staphylinidae, Aleocharinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The studies of alpine and montane Oxypoda species include: 1. On Oxypoda alni Bernhauer, 1940; 2. A new species of the subgenus Oxypoda s. str.; 3. On the synonymy of Oxypoda species described by Scheerpeltz from the Alps. The poorly known species Oxypoda alni Bernhauer is redescribed, aedeagus and spermatheca are figured for the first time. - Oxypoda ignorata sp. n. is described and separated from Oxypoda opaca (Gravenhorst). - A revision of the types of Oxypoda species described by Scheerpeltz from the Alps yielded the following synonymies: bavarica Scheerpeltz, 1956 syn. n. = exoleta Erichson, 1840; huetheri Scheerpeltz, 1956 = exoleta Erichson, 1840; hoelzeli Scheerpeltz, 1963 syn. n. = skalitzkyi Bernhauer, 1902; carnica Scheerpeltz, 1956 syn. n. = brevicornis (Stephens, 1832); glacialis Scheerpeltz, 1956 = densa (Fauvel, 1900); carnorum Scheerpeltz, 1958 = bicolor Mulsant & Rey, 1853. Lectotypes are designated for Oxypoda alni Bernhauer, 1940, Oxypoda huetheri Scheerpeltz, 1956, Oxypoda hoelzeli Scheerpeltz, 1963, and Oxypoda carnica Scheerpeltz, 1956. Nomenclatural Acts alni Bernhauer, 1940 (Oxypoda), Lectotype ignorata Zerche, 1996 (Oxypoda (Oxypoda)), spec. n. bavarica Scheerpeltz, 1956 (Oxypoda (Podoxya)), syn. n. of Oxypoda (Podoxya) exoleta Erichson, 1840 carnica Scheerpeltz, 1956 (Oxypoda (Podoxya)), Lectotype; syn. n. of Oxypoda (Podoxya) brevicornis (Stephens, 1832) hoelzeli Scheerpeltz, 1963 (Oxypoda (Podoxya)), Lectotype; syn. n. of Oxypoda (Podoxya) skalitzkyi Bernhauer, 1902 huetheri Scheerpeltz, 1956 (Oxypoda (Podoxya)), Lectotype now a synonym of Oxypoda (Podoxya) exoleta Erichson, 1840